All Days 2013
DOI: 10.2118/167356-ms
|View full text |Cite
|
Sign up to set email alerts
|

Application of Seismic Attributes in Estimating Gas Resources in Complex Fluvial Channel Reservoirs

Abstract: The purpose of this paper is to show the reserve estimation procedures used by KUFPEC on the NW Shelf of Australia production license WA-49-L, which is currently under development as part of the Chevron's Wheatstone LNG project. The gas in the WA-49-L permit was discovered in a combination of structural and stratigraphic traps of a regional fluvial channel sand complex within the Triassic Mungaroo Formation. These channel sands contain gas trapped on a large structural ridge with up-dip terminations below a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Gamma ray logs have also been used to identify and characterize sand bodies in the EMK field within the Niger Delta region, while seismic reflection data has been used to investigate subsurface fluid flow features and their correlation with hydrocarbon systems in Egypt's Alamein basin [15] [16] [17] [18]. Other studies have focused on characterizing reservoirs in different regions, including fluvial reservoirs in the Laohekou Oilfield, China, fluvial channel systems and gas sand reservoirs in Australia's Carnarvon Basin, and submarine channels and valleys in the eastern Mediterranean Sea [19] [20] [21]. These studies highlight the importance of understanding sedimentation mechanisms and geological structure in deep-water environments, as well as the significance of various tools and data for reservoir characterization and exploration.…”
Section: Introductionmentioning
confidence: 99%
“…Gamma ray logs have also been used to identify and characterize sand bodies in the EMK field within the Niger Delta region, while seismic reflection data has been used to investigate subsurface fluid flow features and their correlation with hydrocarbon systems in Egypt's Alamein basin [15] [16] [17] [18]. Other studies have focused on characterizing reservoirs in different regions, including fluvial reservoirs in the Laohekou Oilfield, China, fluvial channel systems and gas sand reservoirs in Australia's Carnarvon Basin, and submarine channels and valleys in the eastern Mediterranean Sea [19] [20] [21]. These studies highlight the importance of understanding sedimentation mechanisms and geological structure in deep-water environments, as well as the significance of various tools and data for reservoir characterization and exploration.…”
Section: Introductionmentioning
confidence: 99%
“…Many of the gas bearing reservoirs have associated class three AVO anomalies conformable with structure, resulting in "bright spot" and occasional flatspot DHIs. AVO seismic inversion and lithology prediction is commonly used to define both reservoir channel fairways and de-risking exploration (Lamont et al, 2008;Tilbury et al, 2009;Al-Duaij et al, 2013). It has been shown that lithology prediction seismic cubes can be used to directly estimate the sand volume within a stratigraphic interval of the Mungaroo Formation by calculating geobodies with a certain prediction threshold (Shadlow et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The subjectivity is due to channel edges not always being readily identifiable, thin channel associated reservoir not always being recognised and intra-channel heterogeneities affecting the amplitude response. In addition, the predominant class 3 AVO effect exhibited by the Mungaroo reservoirs (Al-Duaij et al 2013) complicates the interpretation of channels near the fluid contacts. Seismic inversion data is commonly used in conjunction with reservoir static and dynamic modelling to help constrain reserve assessments, and has been effectively used both on the Julimar Brunello complex (Al-Duaij et al 2013) and on the Gorgon Field to the southwest (Van Der Weiden, Nayak, & Swinburn, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the predominant class 3 AVO effect exhibited by the Mungaroo reservoirs (Al-Duaij et al 2013) complicates the interpretation of channels near the fluid contacts. Seismic inversion data is commonly used in conjunction with reservoir static and dynamic modelling to help constrain reserve assessments, and has been effectively used both on the Julimar Brunello complex (Al-Duaij et al 2013) and on the Gorgon Field to the southwest (Van Der Weiden, Nayak, & Swinburn, 2012). In addition, there are several case studies in which inversion data has been used to de-risk exploration (Di Luca, et al, 2014), calculate net pay , or use stochastic inversion to assess sand connectivity in a simulation model (Moyen & Doyen, 2009).…”
Section: Introductionmentioning
confidence: 99%